A Laboratory Study on the Modeling of Temperature-Dependent Development and Antioxidant System of Chilo suppressalis (Lepidoptera: Crambidae). Issue 2 (29th March 2018) - Shamakhi, Leila; Zibaee, Arash; Karimi-Malati, Azadeh; Hoda, Hassan
Abstract: The developmental rates of Chilo suppressalis (Walker; Lepidoptera: Crambidae) were investigated at different constant temperatures of 11, 18, 22, 24, 26, 30, 32, 34, and 36°C to find out temperature thresholds, thermal requirements and larval antioxidant responses. The time to complete immature stages separately reduced by raising the rearing temperature except for eggs which showed no significant differences at 30–34°C. Data analysis by traditional and Ikemoto–Takai linear models determined T min of 10.0 and 9.92°C as well as thermal constants of 840.34 and 848.0 DD for the overall immature stages. The models including Analytis, Briere-2, Lactin-2, and Sharpe–Schoolfield–Ikemoto (SSI) calculated T min values of 9.15, 9.57, 10.0, and 11.37°C for overall immature stages while T fast was found to be 33.8, 33.3, 33.7, and 33.0°C, respectively. T max was calculated as 35.12, 34.66, 34.56, 36.84, 34.11, and 35.15°C for Analytis, Briere-2, Lactin-2, SSI, Logan-6, and Logan-10. T opt using SSI was calculated as 24.42°C for total developmental time. The larvae exposure to 34°C in the short-term period demonstrated the highest activities of catalase, peroxidase, and superoxide dismutase compared to control (24°C). Activities of ascorbate peroxidase and glucose-6-phosphate hydrogenase also increased at 34°C in the short-term period for all preparations. The larvae exposed to 34°C in short-term period showed the highest amounts of Malondialdehyde and oxidized and reduced thiols (RSSR/RSH) ratio compared to control. These results may be useful to explain potentially ecological performance of C. suppressalis as the major pest of rice in Iran.